Covariation between air chiller and chicken product microbiota in a poultry processing facility - Birgitte Moen; Annette Fagerlund; Sophie Marie Pursti; Merete Rusås Jensen; Solveig Langsrud (PLoS ONE, 2026)
Chicken products are prone to microbial spoilage, and early detection of deviations in contaminating microbiota can improve quality while reducing waste and customer complaints. In industrial poultry processing, the chiller is a key post-slaughter step but may serve as a source of microbial contamination. In this study the variation in microbial status of the air chiller surface was profiled together with freshly produced and end-of-shelf-life chicken legs and skinless breast fillets across 18 production batches over eleven weeks. Samples were taken early and late shifts on Mondays and Thursdays. The air chiller was cleaned weekly on Fridays. Products were stored under modified atmosphere (60% CO 2 /40% N 2 ) for 21 days at 4˚C, and a subset underwent temperature abuse (8˚C) during the last four days of storage. Microbial community composition was determined using partial 16S rRNA amplicon sequencing. Higher bacterial loads were found on air chiller swabs and fresh products collected at late shift on Thursdays than Mondays (p adj < 0.05). A similar trend was observed for products at the end of shelf-life. At the end of shelf-life, the microbiota in chicken legs was dominated by Carnobacterium , Yersiniaceae and Lactobacillales , whereas breast fillets were dominated by Lactobacillus , Lactobacillales and Carnobacterium . The air chiller microbiota was dominated by Acinetobacter , Psychrobacter and Pseudomonas . Across weeks and sampling times, microbial load and community composition covaried between the air chiller and products, indicating that temporal shifts in the air chiller environment influenced or reflected the product microbiota. These findings identify the air chiller as a critical control point for targeted monitoring and intervention to mitigate spoilage risk. Recommended measures include mid-week cleaning, condensation and aerosol management, and MAP-matched incubation of environmental swabs to reveal CO 2 -tolerant spoilage bacteria.